APPLICATION OF 32 CENTRAL COMPOSITE DESIGN FOR THE FORMULATION OF RAPID SOLUBLE ORODISPERSIBLE FILM OF DIPYRIDAMOLE - AHMAD, FAZIL (International Journal of Applied Pharmaceutics, 2022)
Objective: The aim of this investigation is to formulate, design, optimize and to an evaluation of the rapid soluble orodispersible film (OTF) of dipyridamole (DPI) using the solvent casting method by 32 central composite designs. Methods: Statistical design was used to optimize the preliminary formulations by selecting independent variables such as a polymer (HPMC-E52V, X1) and plasticizer (PEG400, X2) concentration as film-forming polymer and as a plasticizer and the dependent variables such as the release of drug in percentage (Y1), time of disintegration (sec, Y2) and tensile strength (N/m2 Y3). Results: The content of the drug was resulted in the range of 95.05–101 %. The physical properties were found to be colorless and homogenously clear and smooth surface. The folding endurance shown as without any scratches with the pH ranges from 6.35 to 6.75 and the prepared film was not irritated to the oral mucosa. Conclusion: The prepared films showed an optimum time of disintegration that is 25 sec, 96.74% drug release in phosphate buffer of pH 6.8 at initial 5 min and 85.98 % ex-vivo permeation studies after 30 min.